The Potential of Natural Ingredients as Sunscreen: A Narrative Literature Review - Adinda Putri Sabrina; Tania, Evi; Siti Nuryamah; Nia Yuniarsih (HM Publisher, 2022)
Sunlight is an electromagnetic wave that plays a role in producing UV radiation. UV radiation is a major source of skin damage. The utilization of natural ingredients as active ingredients in sunscreen cosmetics is an alternative to chemicals that are also harmful to the skin. Several plants, including Brucea javanica (L.), Family Myrtaceae, Hippobroma Longiflora (L) G. Don, Kaempferia galanga L, and Eucheuma cottonii. Doty and Zea mays L. have the potential to be developed as a sunscreen.